12-year analysis of incidence, microbiological profiles and in vitro antimicrobial susceptibility of infectious keratitis: the Nottingham Infectious Keratitis Study. Issue 3 (24th June 2020) - Ting, Darren Shu Jeng; Ho, Charlotte Shan; Cairns, Jessica; Elsahn, Ahmad; Al-Aqaba, Mouhamed; Boswell, Tim; Said, Dalia G; Dua, Harminder Singh
Abstract : Background/aims: To examine the incidence, causative microorganisms and in vitro antimicrobial susceptibility and resistance profiles of infectious keratitis (IK) in Nottingham, UK. Methods: A retrospective study of all patients who were diagnosed with IK and underwent corneal scraping between July 2007 and October 2019 (a 12-year period) at a UK tertiary referral centre. Relevant data, including demographic factors, microbiological profiles and in vitro antibiotic susceptibility of IK, were analysed. Results: The estimated incidence of IK was 34.7 per 100 000 people/year. Of the 1333 corneal scrapes, 502 (37.7%) were culture-positive and 572 causative microorganisms were identified. Sixty (4.5%) cases were of polymicrobial origin (caused by ≥2 different microorganisms). Gram-positive bacteria (308, 53.8%) were most commonly isolated, followed by Gram-negative bacteria (223, 39.0%), acanthamoeba (24, 4.2%) and fungi (17, 3.0%). Pseudomonas aeruginosa (135, 23.6%) was the single most common organism isolated. There was a significant increase in Moraxella spp (p<0.001) and significant decrease in Klebsiella spp (p=0.004) over time. The in vitro susceptibilities of Gram-positive and Gram-negative bacteria to cephalosporin, fluoroquinolone and aminoglycoside were 100.0% and 81.3%, 91.9% and 98.1%, and 95.2% and 98.3%, respectively. An increase in resistance against penicillin was observed in Gram-positive (from 3.5% to 12.7%; p=0.005) and Gram-negative bacteria (from 52.6% to 65.4%; p=0.22). Conclusion: IK represents a relatively common and persistent burden in the UK and the reported incidence is likely underestimated. Current broad-spectrum antimicrobial treatment provides a good coverage for IK, although challenged by some level of antimicrobial resistance and polymicrobial infection.